2007
DOI: 10.1016/j.neuroscience.2007.04.036
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal cocaine exposure enhances responsivity of locus coeruleus norepinephrine neurons: Role of autoreceptors

Abstract: Children exposed to cocaine during gestation have a higher incidence of neurobehavioral deficits. The neurochemical bases of these deficits have not been determined, but the pharmacology of cocaine and the nature of the abnormalities suggest that disruptions in catecholaminergic systems may be involved. In the current study, we used a rat model of prenatal cocaine exposure to examine the impact that this exposure has on the locus coeruleus (LC) noradrenergic system in offspring. Pregnant rats received twice-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…Whether repeated restraint leads to enhanced NE activity is unknown, but this different stress paradigm or the much higher doses of clonidine (Aghajanian & VanderMaelen, 1982; Pavcovich et al ., 1990; Lacroix et al ., 1991; Pineda et al ., 1997) may explain the contrasting leftward shift of the dose–response curve for clonidine‐evoked inhibition of LC neurons reported following repeated restraint (Pavcovich et al ., 1990). The present demonstration of decreased autoreceptor function is consistent with the reduction of autoinhibitory control over LC neuronal activity, as suggested by decreased autoreceptor antagonism following repeated tail shock exposure (Simson & Weiss, 1988) and in a prenatal cocaine model leading to enhanced noradrenergic activation (Elsworth et al ., 2007). Furthermore, it complements previous neurochemical and electrophysiological changes in the noradrenergic system following cold exposure (Nisenbaum et al ., 1991; Nisenbaum & Abercrombie, 1992; Gresch et al ., 1994; Finlay et al ., 1997; Mana & Grace, 1997; Jedema et al ., 1999, 2001; Jedema & Grace, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Whether repeated restraint leads to enhanced NE activity is unknown, but this different stress paradigm or the much higher doses of clonidine (Aghajanian & VanderMaelen, 1982; Pavcovich et al ., 1990; Lacroix et al ., 1991; Pineda et al ., 1997) may explain the contrasting leftward shift of the dose–response curve for clonidine‐evoked inhibition of LC neurons reported following repeated restraint (Pavcovich et al ., 1990). The present demonstration of decreased autoreceptor function is consistent with the reduction of autoinhibitory control over LC neuronal activity, as suggested by decreased autoreceptor antagonism following repeated tail shock exposure (Simson & Weiss, 1988) and in a prenatal cocaine model leading to enhanced noradrenergic activation (Elsworth et al ., 2007). Furthermore, it complements previous neurochemical and electrophysiological changes in the noradrenergic system following cold exposure (Nisenbaum et al ., 1991; Nisenbaum & Abercrombie, 1992; Gresch et al ., 1994; Finlay et al ., 1997; Mana & Grace, 1997; Jedema et al ., 1999, 2001; Jedema & Grace, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence for the involvement of the noradrenergic system in the retrieval of memory (Sara and Devauges, ). Presynaptic α 2 ‐adrenoceptors function as autoreceptors in the LC (Elsworth et al , ) and the α 2 ‐adrenoceptor agonist clonidine, per se, impaired the memory retention (Jafari‐Sabet et al , ). We also found that clonidine administered within the LC inhibited memory retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…While the underlying mechanisms for these findings remain unknown, the noradrenergic system may be involved. PCE has been shown to affect the noradrenergic system (Elsworth, et al 2007; Foltz, et al 2004; Seidler and Slotkin 1992; Snow, et al 2004), which in turn may influence pubertal development. Norepinephrine plays a role in regulating the hypothalamus (Christman and Gisolfi 1985; Oishi 1979; Tsigos and Chrousos 2002), which contains cells that produce gonadotropin releasing hormones that regulate pubertal development, particularly the onset of puberty (Plant 2002).…”
Section: Discussionmentioning
confidence: 99%